EFFECT OF EXPORTS, IMPORTS OF OIL AND GAS PRODUCTS, INFLATION, ON ECONOMIC GROWTH - Anjani Cantika Panji Anggoro (Transpublika Publisher, 2022)
This study aims to analyze the effect of oil and gas exports, oil and gas imports, and inflation on Indonesia's economic growth. This study employs secondary data, which consists of information retrieved or compiled by researchers from preexisting sources. The method used to analyze the relationship between endogenous and exogenous variables is a dynamic model with Vector Error Correction Approach Model (VECM). The findings revealed that in the long term and short term show that the Export of Oil and Gas Products has a positive effect on Indonesia's Economic Growth. In the long term and in the short term, imports of oil and gas negatively affect Indonesia's economic growth. Likewise, in the long term and short term, inflation negatively affects Indonesia's economic growth.